Formulation and Activity Test of Cold Shake Noni Fruit Extract (Morinda citrifolia L.): Formulasi dan Uji Aktivitas Antioksidan Bedak Dingin Kocok Ekstrak Buah Mengkudu (Morinda citrifolia L.) - Rasdawati; Nurisyah; Sisilia Teresia Rosmala Dewi (Akademi Farmasi Surabaya, 2023)
Noni fruit (Morinda citrifolia L.) is known to contain flavonoids, alkaloids and saponins. Flavonoid compounds function as antioxidants. This study aims to determine the antioxidant activity and stability of whipped cold powder extract of Noni Fruit (Morinda citrifolia L.). Noni fruit (Morinda citrifolia L.) was extracted using the maceration method using 96% ethanol, then evaporated using a rotary evaporator. The preparation of whipped cold powder Noni Fruit extract was made in 3 formulas with various concentrations, F I (3%), F II (6%) and F III (9%). The cold whipped powder formula is made without using extract as a base (F 0). Test the antioxidant activity of the DPPH solution as measured by a UV-Vis spectrophotometer at a maximum wavelength of 519 nm, the results of the analysis showed the average % inhibition of F I was 76.43%, F II was 81.69%, F III was 81.81% while the chilled powder base (F 0) was 9.21%. Of all the formulas that have the most effective antioxidant activity is F II with a concentration of 6%. Next, an evaluation of the whipped cold powder preparations was carried out, namely organoleptic testing, homogeneity, pH, viscosity, and adhesion of all the cold whipped powder preparations that met the requirements.